Qualitative changes of anticonvulsant action of felbamate during development in rats - Haugvicová, R; Kubová, H; Mares, P (Brain & development, 1998)
The anticonvulsant action of felbamate (25, 50, 100 and 150 mg/kg i.p.) was tested against motor seizures induced by pentylenetetrazol in five age-groups of rats (7, 12, 18, 25 and 90 days old). In adult rats, felbamate suppressed generalized tonic-clonic seizures leaving intact minimal clonic seizures. In all groups of rat pups felbamate exhibited a specific action against the tonic phase of generalized tonic-clonic seizures. In addition, the highest dose of felbamate was found to suppress minimal seizures in 18-day-old rats. The changes of felbamate action during ontogeny might be due to multiple mechanisms of anticonvulsant action with an uneven developmental profile.
Keywords: záchvaty; Animals, Newborn; Male; Aging; konvulziva; Rats, Wistar; Felbamate; Phenylcarbamates; vztah mezi dávkou a účinkem léčiva; mužské pohlaví; potkani Wistar; felbamát; Seizures; novorozená zvířata; Anticonvulsants; propylenglykoly; krysa rodu Rattus; Convulsants; Animals; Pentylenetetrazole; zvířata; Rats; antikonvulziva; stárnutí; pentylentetrazol; fenylkarbamáty; Propylene Glycols; Dose-Response Relationship, Drug